Improvement of the microstructure and mechanical properties of bioceramic scaffolds using electrohydrodynamic spraying with template modification - Muthutantri, Anushini I.; Edirisinghe, Mohan J.; Boccaccini, Aldo R. (Journal of the Mechanical Behavior of Biomedical Materials, 2010)
Porous scaffolds play a key role in tissue engineering (TE) approaches and new processing methods and materials are constantly being developed to cater for the wide range of specifications and requirements. Electrospraying is a relatively new processing method used for producing open-pore scaffolds. In this work, the electrospraying technique was manipulated to make the process more efficient, and the effect of spraying time on the pore size and strut thickness of zirconia scaffolds was explored. Scaffolds of adequate pore size and interconnectivity, with an average compressive strength of ∼7.5 MPa, by electrospraying for only 10 min are reported. The effect of modifying the sacrificial template on the microstructure and mechanical properties of the sintered scaffolds was also investigated. A combination of template surface hydroxylation and improved conductivity produced a thicker ceramic coating, leading to enhanced mechanical properties. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.improv